الملامح اللسانية في الفكر اللغوي العربي - عبد القاهر الجرجاني في كتابه "دلائل الإعجاز" أنموذجاً- - بصل, محمد; بلـه, فاطمة (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف هذا البحث إلى تقصي ملامح الفكر العربي اللساني; لأن اللغة العربية لغة علم، لا نفرض عليها القوالب اللسانية الغربية الجاهزة، إنما تكون مبادئ اللسانيات الغربية بمنزلة جسر لقراءة لغوية في التراث اللغوي العربي. وقد وقع الاختيار على رمز من رموز هذا التراث اللغوي، هو عبد القاهر الجرجاني في كتابه "دلائل الإعجاز"، لندرك أن كثيراً من المقولات اللسانية قد سبق للفكر اللغوي العربي أن توصل إليها، فكادت النتائج التي أثبتها الجرجاني تتطابق مع كثير من المقولات التي جاء بها "فردينان ده سوسر" و "رومان جاكبسون" و"جون كوهن"...... وليس الغرض من هذه الدراسة عقد موازنة بين علماء اختلفوا في الأزمنة والبيئة، والثقافة، إنما هي للتأكيد أن الدراسة التحليلية للمادة اللغوية العربية قد سبقت بلورة مقولات لسانية عامة، فجاءت الأفكار اللسانية العربية تحمل طابع الأصالة، ولم تأتِ نتيجة تطبيق نظرية لسانية غربية. This research aims to pursue the features of the Arabic lingual thought. Because the Arabic Language is a language of Knowledge and science, no already-made western lingual forms can be imposed on it; but the western lingual principles can be a bridge for a lingual reading in the Arabic linguistic heritage. One of the Arabic lingual symbols been chosen who is Abdulkaher Aljirjani in his Book " Inimitability Attestations" in order to realize that many of the lingual sayings had been already reached by the Arabic linguistic thought. Thus, the results proved by Aljirjani conform to many sayings proposed by Ferdinand de Saussure, Roman Jacobson and John Cohen … The purpose of this study is not to balance among some scientists from different times, environments and cultures but to assure that the analytic study of the Arabic Linguistic material had preceded the crystallization of general lingual sayings. So, the Arabic thoughts about linguistics sound totally genius because it is not a result of applying a western lingual theory.